Challenges in secondary prevention of cardiovascular diseases: A review of the current practice. (1st February 2015) - Piepoli, Massimo F.; Corrà, Ugo; Abreu, Ana; Cupples, Margaret; Davos, Costantinos; Doherty, Patrick; Höfer, Stephan; Garcia-Porrero, Esteban; Rauch, Bernhard; Vigorito, Carlo; Völler, Heinz; Schmid, Jean-Paul; et al.
Abstract: With the changing demography of populations and increasing prevalence of co-morbidity, frail patients and more complex cardiac conditions, the modern medicine is facing novel challenges leading to rapid innovation where evidence and experiences are lacking. This scenario is also evident in cardiovascular disease prevention, which continuously needs to accommodate its ever changing strategies, settings, and goals. The present paper summarises actual challenges of secondary prevention, and discusses how this intervention should not only be effective but also efficient. By this way the paper tries to bridge the gaps between research and real-world findings and thereby may find ways to improve standard care. Highlights: More investment in preventive measures and facilities, more information on prevention within the cardiologists' community. Cardiologists' involvement in implementing health policies of secondary prevention at continental and each country levels. Well designed pathways for the continuity of care. Formally shared responsibilities for all professionals involved, including invasive and surgical colleagues. Minimum standards in terms of duration and quality of services delivered, within certified centres.